2013
DOI: 10.3892/ijo.2013.1920
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate promotes apoptosis and expression of the caspase 9a splice variant in PC3 prostate cancer cells

Abstract: Growing evidence suggests that the flavonoid epigallocatechin-3-gallate (EGCG), notably abundant in green tea, has health-promoting properties. We examined the effect of EGCG on cell survival and apoptosis in the prostate cancer cell line PC3. Cell survival was reduced and apoptosis increased significantly with a low dose of 1 µM EGCG. The ability of the anticancer drug cisplatin to promote apoptosis was enhanced by EGCG. Furthermore, EGCG, both alone and in combination with cisplatin, promoted the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…It is used to treat many types of solid cancer, such as ovary, bladder, lung and colorectal cancers. 16 However, the efficacy of cisplatin therapy for metastatic bladder cancer is limited because of intrinsic or acquired drug resistance. 17,18 Therefore, combination therapy based on the synergistic effect between drugs has been used to overcome such drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is used to treat many types of solid cancer, such as ovary, bladder, lung and colorectal cancers. 16 However, the efficacy of cisplatin therapy for metastatic bladder cancer is limited because of intrinsic or acquired drug resistance. 17,18 Therefore, combination therapy based on the synergistic effect between drugs has been used to overcome such drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological investigations and experimental studies have shown that green tea has chemopreventive effects for a wide range of malignancies, including lung, stomach, breast, prostate, pancreatic, ovarian, liver, colorectal and skin cancer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Mechanistic studies indicate that EGCG, the major component of green tea, appears to be the primary active ingredient responsible for its biological effects.…”
Section: Introductionmentioning
confidence: 97%
“…Epigallocatechin-3-gallate (EGCG) is a water-soluble catechin, which suppresses the multiplication of cancer cells and induces apoptosis (3)(4)(5). EGCG suppressed adhesion and invasion of hepatocarcinoma cells through antioxidant activity (6).…”
Section: Introductionmentioning
confidence: 99%